2018
DOI: 10.1186/s40608-018-0197-1
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicinoids supplementation decreases percent body fat and fat mass: adjustment using covariates in a post hoc analysis

Abstract: BackgroundCapsaicinoids (CAPs) found in chili peppers and pepper extracts, are responsible for enhanced metabolism. The objective of the study was to evaluate the effects of CAPs on body fat and fat mass while considering interactions with body habitus, diet and metabolic propensity.MethodsSeventy-five (N = 75) volunteer (male and female, age: 18 and 56 years) healthy subjects were recruited. This is a parallel group, randomized, double-blind, placebo controlled exploratory study. Subjects were randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
0
18
0
12
Order By: Relevance
“…Three out of the 12 included studies had a high ROB, whereas the remaining nine studies had some ROB concerns. Bias arising from the randomization process was low in three studies 16,20,25 , eight studies had some ROB concerns 17,19,[21][22][23][24]26,27 , and one study had a high ROB 18 because the only information in this article was a sentence stating that the study was randomized. Bias due to deviations from the intended intervention were low in all studies except for one 17 , in which allocation concealment was not reported.…”
Section: Description Of Included Studiesmentioning
confidence: 95%
See 3 more Smart Citations
“…Three out of the 12 included studies had a high ROB, whereas the remaining nine studies had some ROB concerns. Bias arising from the randomization process was low in three studies 16,20,25 , eight studies had some ROB concerns 17,19,[21][22][23][24]26,27 , and one study had a high ROB 18 because the only information in this article was a sentence stating that the study was randomized. Bias due to deviations from the intended intervention were low in all studies except for one 17 , in which allocation concealment was not reported.…”
Section: Description Of Included Studiesmentioning
confidence: 95%
“…Out of the 12 studies, five were conducted in the United States 18,19,[21][22][23] , three in Korea 17,24,25 , two in Japan 20,26 , one in Australia 27 , and one in China 16 . Ten of the studies were parallel-arm studies 16,17,[19][20][21][22][23][24][25][26] whereas the other two were crossover studies 18,27 . Ten studies were conducted on individuals with body mass index (BMI) above 25 kg/m [21][22][23][24][25]27 , and two studies were conducted on healthy individuals with BMI below 25 kg/m 220, 26 .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chili pepper is widely cultivated in South America, Asia, and Africa as well as some Mediterranean countries where it is used in hundreds of food recipes and as a condiment either fresh or in processed forms, such as dried chili powder, hot sauce, and pickle. The average chili pepper consumption in some countries is, for example, 20 g/person/day in Mexico, 8 g/person/day in Korea, 5 g/person/day in Thailand, 2.5 g/person/day in India, and 0.05 to 0.50 g/person/day in the United States (Ludy & Mattes, ; Othman, Ahmed, Habila, & Ghafar, ; Rogers et al., ). Thailand has the fifth largest area dedicated to chili pepper production at 92,126 ha, and is the second largest producer of red and dried chili at 349,397 tons per year, which is worth over $3 million in yearly exports (FAO, ; MOC, ).…”
Section: Introductionmentioning
confidence: 99%